21 : the inside story of six M.I.T. students who took Vegas for millions - Mezrich, Ben, 1969-; Heller, Johnny; Simon & Schuster Audio (Firm) (New York : Simon & Schuster Audio, 2008)
Presents the story of a group of M.I.T. students who put their card-counting skills to work in Las Vegas to win millions of dollars
Unabridged
Originally published in print form as: Bringing down the house
Read by Johnny Heller
Keywords: Massachusetts Institute of Technology -- Students -- Biography; Cardsharping; Gambling -- Nevada -- Las Vegas; Gamblers -- Massachusetts -- Cambridge -- Biography